2020
DOI: 10.3897/zoologia.37.e50834
|View full text |Cite
|
Sign up to set email alerts
|

The puzzling occurrence of the upside-down jellyfish Cassiopea (Cnidaria: Scyphozoa) along the Brazilian coast: a result of several invasion events?

Abstract: The massive occurrence of jellyfish in several areas of the world is reported annually, but most of the data come from the northern hemisphere and often refer to a restricted group of species that are not in the genus Cassiopea. This study records a massive, clonal and non-native population of Cassiopea and discusses the possible scenarios that resulted in the invasion of the Brazilian coast by these organisms. The results indicate that this jellyfish might have invaded the Brazilian coast multiple times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…In the case of Cassiopea andromeda, although we detected its eDNA in the Florida Keys some workers have suggested that C. xamachana and C. andromeda may be the same species (Holland et al, 2004). However, in our analysis, consensus sequences of putative C. andromeda and C. xamachana diverge by roughly 4%, raising the hypothesis that a separate species is present, which is corroborated by recent findings (Stampar et al, 2020). The fact that resident Cassiopea species, C. xamachana and C. frondosa, can be readily distinguished based on both morphology and genetics is evidence for two reproductively isolated species.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the case of Cassiopea andromeda, although we detected its eDNA in the Florida Keys some workers have suggested that C. xamachana and C. andromeda may be the same species (Holland et al, 2004). However, in our analysis, consensus sequences of putative C. andromeda and C. xamachana diverge by roughly 4%, raising the hypothesis that a separate species is present, which is corroborated by recent findings (Stampar et al, 2020). The fact that resident Cassiopea species, C. xamachana and C. frondosa, can be readily distinguished based on both morphology and genetics is evidence for two reproductively isolated species.…”
Section: Discussionsupporting
confidence: 88%
“…The fact that resident Cassiopea species, C. xamachana and C. frondosa, can be readily distinguished based on both morphology and genetics is evidence for two reproductively isolated species. C. andromeda was originally described from the Red Sea, from where it has recently spread throughout the world to warm, coastal waters, possibly introduced at the microscopic life stage in ballast water or as polyps on ship hulls (Holland et al, 2004;Stampar et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…andromeda (black) and C . xamachana (white) distributions from sequences published in relevant scyphozoan or Cassiopea specific phylogenies from 2004–2022 [ 3 , 6 , 13 , 17 , 29 ]. Locations with both recorded as black-and-white.…”
Section: Resultsmentioning
confidence: 99%
“…xamachana and C . andromeda populations, but these were found in separate sampling efforts [ 17 , 29 , 32 ]. Locations with Cassiopea , especially those with a paucity of sequences, may present the sort of assemblages already identified here in the Florida Keys, Hawai’i, Brazil, the Philippines and Palau, and may require multiple rounds of sampling to parse [ 3 , 6 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…This species is an epibenthic scyphozoan with a maximum umbrella diameter of about 30 cm commonly found in tropical and subtropical shallow coastal ecosystems such as mangroves, estuaries, and sandy mudflats. This species has a metagenetic cycle with the following phases: planula, benthic polyp, ephyra, and adult medusa [ 7 ].…”
Section: Introductionmentioning
confidence: 99%